IDENTIFICATION OF SAFETY ALERT BY MONITORING ANALYTICAL PARAMETERS AND HIGH-RISK DRUGS - Vilaplana, Vicente Escudero-; AntÃºnez, MarÃa GÃ³mez-; GarcÃa, Esther DurÃ¡n-; MÃguez, Antonio MuiÃ±o-; SÃ¡ez, MarÃa Sanjurjo- (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Early detection of adverse drug reactions (ADR) increases patient safety. Our objective was to identify ADR by monitoring laboratory parameters and high-risk drugs. We carried out a two-month prospective observational study in a Internal Medicine Department, with daily recording of drugs prescribed and the following parameters: Na, K, Ca, serum creatinine, glomerular filtration rate (GFR), INR, glucose, haemoglobin, platelets, ALT, AST, bilirubin, GGT, alkaline phosphatase, TSH, T4, and blood digoxin. High-risk drugs were closely monitored. 52 patients included, of whom 46.2% experienced an ADR. We observed an association with drugs in 25.5%, as follows: reduction in GFR, 26.9% (associated with loop diuretics [41.7%], angiotensin-converting enzyme [ACE] inhibitors [33.3%], angiotensin II receptor blockers [ARB] [16.6%], andanti-diabetic drugs [8.3%]); hypokalemia, 22.3% (associated with loop diuretics [50.0%], potassium-free fluid [37.5%], and salbutamol [12.5%]); hyperkalemia, 14.4% (associated with ACE inhibitors [60.0%] and ARB [40.0%]); INR out of range, 10.8% (associated with drug interactions [66.7%]); hyperglycemia, 8.1% (associated with corticosteroids [66.7%] and anti-diabetic drugs [33.3%]); and other conditions, 18.8%. We conclued that patient safety could be improved by implementing warnings in electronic prescriptions in cases of a decrease in GFR or modification of potassium levels in patients who are prescribed loop diuretics, ACE inhibitors, or ARBs.Key words: Adverse drug reaction, clinical decision support, high-risk drug, safety